서비스기업 종업원의 표면행위가 이직의도에 미치는 영향에 관한 연구: 지각된 사회적 지원의 조절효과를 중심으로 - 김완민; 강성호; 이한근; Kim, Wan-Min; Kang, Seong-Ho; Lee, Han-Geun (Journal of distribution science, 2017)
Purpose - Previous studies related to emotional labor of salespeople have mainly focused on identifying the antecedents of emotional exhaustion and turnover intention and exploring the mitigating effects salespeople's motivation on emotional exhaustion and turnover intention. They also demonstrates that there are different roles for moderating in social support, which means mental/physical support related to the job in supervisors, colleagues and organizations. The purpose of this paper is to investigate how service employees' surface acting affect turnover intention through emotional exhaustion. Another important objective of this paper is to investigate whether perceived social support moderates 1) the relationship between surface acting and emotional exhaustion 2) the relationship between emotional exhaustion and turnover intention. Research design, data, and methodology - To test the hypotheses, we collected the data from Korean insurance company sales employees. A total of 235 responses were received, from which 220 usable responses were obtained after list-wise deletion. Working with a sample of 220 responses, structural equation modeling was employed to empirically test research hypotheses( The relationship between surface acting and emotion exhaustion, The relationship between emotion exhaustion and turnover intention, The moderating effect of perceived social support(PSS) on the relationship between surface acting and emotion exhaustion, and The moderating effect of perceived social support(PSS) on the relationship between emotion exhaustion and turnover intention. SPSS 22.0 and AMOS software were used in these data analysis. Results - The service employees' surface acting was positively related to the emotional exhaustion; in turn, the service employees' feelings on emotional exhaustion are positively related to turnover intention. In addition, Perceived Social Support significantly moderated the relationship between surface acting and emotional exhaustion. However, perceived social support has a non-significant moderating effect on the path from emotional exhaustion to turnover intention. On the basis of these results, the following conclusion can be drawn. First, distribution service companies will be needed the administrative efforts to offer counseling programs and space to provide their members with enough rest in experiencing psychological pain due to the salespeople's surface acting. Also, it is necessary for distribution service companies to identify and share the examples of successfully solving emotional exhaustion caused by salespeople's surface acting.